Peran Kelompok Tani dalam Pengembangan Padi Rojolele Srinuk (Studi Kasus Desa Delanggu, Kecamatan Delanggu, Kabupaten Klaten) - Melga Yudistiya Amanatullah Pratomo; Retno Setyowati; Joko Winarno (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Klaten Regency is one of the rice-producing areas and has superior rice, namely Rojolele Srinuk rice. The rice-producing area of Rojolele Srinuk is Delanggu Village which is located between the Solo - Yogyakarta road and is on the slopes of Mount Merapi. The Ngudi Makmur I and Ngudi Makmur II farmer groups are farmer groups located in Delanggu Village which have the Rojolele Srinuk rice development program in collaboration with the Sanggar Rojolele Delanggu and were appointed directly from the Klaten Regency Agriculture Service. Empowerment of farming communities in the development of Rojolele Srinuk rice is considered to be able to produce a change in the mindset of farmers not to use chemicals in rice cultivation. This study aims to reveal the role of farmer groups in the development of Rojolele Srinuk rice and to reveal the empowerment efforts carried out. This study uses a qualitative basic method with a descriptive approach and uses a case study research design. The research location is in Delanggu Village, especially in the Ngudi Makmur Farmer Group. The results showed that the role of the Ngudi Makmur farmer group in the development of Rojolele Srinuk rice was carried out according to its role for the success of Rojolele Srinuk organic rice. Efforts by farmer groups in empowering rice farmers, Rojolele Srinuk. Efforts were made from the beginning of the development of Rojolele Srinuk rice to downstream agricultural products.